The role of state programs in NIBRS data quality: a case study of two states - Barnett-Ryan, Cynthia (Journal of contemporary criminal justice, 2008)
This study explores the question of how the organization of state programs might positively influence the data quality of the state's incident-based reporting data and its National Incident-Based Reporting System (NIBRS) data submissions. To investigate this topic, the programs of two states (Tennessee and Vermont) identified as adept at resolving data quality issues are described. These descriptions show that these two state programs have taken measures to implement the quality assurance programs and procedures recommended in The Blueprint for the Future of the Uniform Crime Reporting Program: Final Report of the UCR Study. Given that some states have undertaken very different and very aggressive quality control programs, subsequent research should be done to assess the effects of these programs on the quality of NIBRS submissions.